Antibacterial Activity and Preliminary Phytochemical Screening of Forest Chili Leaf (Piper caninum Bl.) Ethanol Extract against Staphylococcus epidermidis - Shanzet, Flavia Fionessa Falenda; Darmayasa, Ida Bagus Gede; Suriani, Ni Luh; Wiadnyani, Anak Agung Istri Sri; Ho, Ting Seng; Rusdianasari, Rusdianasari; Mariani, Mariani (Tropical Plantation Journal, 2024)
Forest chili leaves (Piper caninum Bl.) has a potential to become an alternative to conventional antibiotics. This study aims to determine the Minimum Inhibitory Concentration (MIC) of forest chili leaf extract, assess the Lethal Concentration (LC50), and analyze the phytochemical composition of the extract. This study also conducted a Completely Randomized Design (CRD) with four repetitions. The agar well diffusion method is used in this study with various concentrations such as T1 ethanol 96% (negative control), T2 (5% concentration), T3 (10% concentration), T4 (15% concentration), T5 (20% concentration), T6 (25% concentration), and T7 Ciprofloxacin 1% (positive control). Data were subjected to ANOVA at a significance level of 5% and further analyzed using Duncan's test. The results showed that all concentrations of forest chili leaf extract (P. caninum Bl.) exerted a statistically significant effect (P 0.05) against Staphylococcus epidermidis bacteria. The research found that the most effective concentration to inhibits S. epidermidis is at 25%, which generates an inhibitory zone of 25.38 ± 0.52 mm. The estimated MIC value for forest chili leaf extract against S. epidermidis was found to be 0.2%, producing an inhibitory zone of 6.38 ± 0.32 mm. Additionally, the calculated LC50 value was 0.26%. Phytochemical screening revealed the presence of various bioactive compound groups in the forest chili leaf extract, including alkaloids, flavonoids, phenols, tannins, and steroids.